2006
DOI: 10.2340/00015555-0098
|View full text |Cite
|
Sign up to set email alerts
|

Important Factors for Pain during Photodynamic Therapy for Actinic Keratosis

Abstract: Photodynamic therapy (PDT) is an efficient treatment for actinic keratosis. A common problem, however, is pain. The aim of this study was to investigate pain during PDT for actinic keratosis. The possibility of using capsaicin cream for pain relief was also assessed. Pain was investigated during aminolaevulinic acid PDT in 91 patients. Size, redness, scaling and induration of the lesions were recorded. Maximum pain during treatment was registered, using a visual analogue scale (0-10). The pain-reducing efficac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
109
3
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(124 citation statements)
references
References 26 publications
10
109
3
2
Order By: Relevance
“…The interindividual difference in size might have biased the results by influencing the pain intensity [4,5]. However, other authors have already shown that the pain intensity is strongly dependent on the localization [2,4,6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The interindividual difference in size might have biased the results by influencing the pain intensity [4,5]. However, other authors have already shown that the pain intensity is strongly dependent on the localization [2,4,6].…”
Section: Discussionmentioning
confidence: 99%
“…The main adverse effect in PDT treatment is pain. It has been shown that pain intensity depends on the localization [2,3], size [3,4,5], histological type [4], redness [5] and protoporphyrin IX (PpIX) fluorescence [6] of the treated lesion. Also different light sources [7,8,9], fluence rates [6] and photosensitizing agents [10,11] affect the pain additionally.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the limited number of lesions in our report, the lesions could not be adequately subdivided in different anatomical zones. This may also degrade the correlation between the PpIX fluorescence and the pain since it has been reported that anatomical innervation differences may play an important role [37,57]. …”
Section: Discussionmentioning
confidence: 99%
“…Because pain is the main adverse effect for this treatment modality, a tablet of anti-inflammatory drug (Méfénacide®, 500 mg) was given to each patient 1 h before treatment [35,37,38,39,40]. Additionally the lesions were sprayed with cold water (approx.…”
Section: Methodsmentioning
confidence: 99%
“…15 Pain can be more severe when a larger field is treated with PDT. 12 Kasche 16 demonstrated that pain during activation can be such that patients request discontinuation of treatment before reaching the required light dose has been reached. This was more likely if the patient was being treated with aminolevulonic acid (ALA) than if treated with methyl aminolevulinate (MAL).…”
Section: Introductionmentioning
confidence: 99%